Modelling surface color discrimination under different lighting environments using image chromatic statistics and convolutional neural networks - Ponting, S; Morimoto, T; Smithson, H (Optical Society of America, 2023)
We modeled discrimination thresholds for object colors under different lighting environments [1]. Firstly we built models based on chromatic statistics, testing 60 models in total. Secondly we trained convolutional neural networks (CNNs), using 160,280 images labeled either by the ground-truth or by human responses. No single chromatic statistics model was sufficient to describe human discrimination thresholds across conditions, while human-response-trained CNNs nearly perfectly predicted human thresholds. Guided by region-of- interest analysis of the network, we modified the chromatic statistics models to use only the lower regions of the objects, which substantially improved performance.